A Primary Extraskeletal Osteosarcoma of the Spleen: Rare Case Report - Pan, Xian; Wang, Han-Lu; Lin, Shi-Ming; Lin, Jia-Li; Ruan, Dan-Dan; Zhang, Jian-Hui; Chen, Ting; Luo, Jie-Wei; Fang, Zhu-Ting (Frontiers in Oncology, 2022)
Extraskeletal osteosarcoma is a rare malignant soft-tissue sarcoma that is difficult to diagnose. Surgery is a common treatment, although chemotherapy and radiotherapy are also used. Patients at risk of bleeding can undergo embolization combined with resection. The occurrence of primary splenic extraskeletal osteosarcoma in humans does not seem to have been reported in the literature. A 50-year-old woman who complained of pain in the left upper abdomen for 1 day was initially diagnosed with “splenic hemangioma with a high possibility of rupture and bleeding” and urgently underwent digital subtraction angiography, combined with splenic arteriography and embolization. Abdominal pain worsened 2 days postoperatively, with a hemoglobin level of 106.0 g/L. Consequently, emergency laparotomy combined with splenectomy was performed. The clinical and imaging features, pathological diagnosis, and embolization treatment of this case were analyzed retrospectively. CT of the upper abdomen revealed splenomegaly, an irregular low-density shadow in the spleen, and a flake-like calcification in the lateral margin of the left kidney. Nuclear MRI of the upper abdomen showed splenomegaly and a mass (approximately 8.4 cm × 5.7 cm × 6.3 cm) below the spleen with clear boundaries—this exhibited an uneven signal, which was slightly low in T1-weighted imaging (T1WI) and slightly high in T2-weighted imaging (T2WI). Several small cystic lesions or cystic cavities were observed in the mass, which exhibited a longer T2 signal. During the enhanced scan, the signal of the lesion showed progressive enhancement, and the enhancement range increased in the delayed phase scan, as well as a hematoma below the spleen capsule and calcification below the lesion (nodular T1WI/T2WI hypointense, approximately 3.3 cm × 3.6 cm). Postoperative biopsy pathology showed splenic soft tissue tumor: at low magnification, the multinucleated giant cells were scattered; at medium magnification, osteoclast-like multinucleated giant cells were observed; and at high magnification, lace- or grid-like tumor osteogenesis was detected. Immunohistochemistry showed that the expression of CD31, CD34, F8, s-100, desmin, SMA, and CD99 was negative, whereas the expression of β-catenin, BCL-2, SATB-2, and P16 was positive. CD68 and MDM-2 showed low expression, while 50% of the cells were positive for Ki-67 expression. No abnormal concentration of radioactivity was found on the bone scan with 99mTc-MDP after the operation, further ruling out the occurrence of other bone tumors. The patient was diagnosed with primary extraskeletal osteosarcoma. It is necessary for multidisciplinary teams to diagnose malignant extraskeletal osteosarcomas.